Obsession [compact disc, unabridged] - Woods, Stuart; Battles, Brett (Woods, Stuart. Teddy Fay novel., 2023)
Filmmakers in California look to expand the studio by making a deal with a Croatian billionaire. But the magnate's wife is kidnapped, and the pressure is on Teddy Fay to save the woman, and the studio.